Adsorption Behaviour of XDA-200 Resin Toward p-Nitrophenol in Aqueous Solution - Zheng, Zhanwang; Xiong, Chunhua; Yao, Caiping (Asian Journal of Chemistry, 2010)
The adsorption behaviour of a colloidal solid particle of adsorption resin XDA-200 for p-nitrophenol was carried out using batch and column techniques. After characterization by direct photometric studies, the static and dynamic adsorption behaviour of p-nitrophenol onto adsorption resin XDA-200 was investigated. The adsorption was optimized with respect to pH, contact time and oscillation frequency. Maximum adsorption capacity was achieved from solution of pH 3-8 after 5.5 h agitation time. The adsorption behaviour of XDA-200 resin for p-nitrophenol obeyed both the Freundlich and Langmuir isotherms. The variation of the equilibrium constant ‘D’ with temperatures between 288 and 308 K yields values of ΔH = -7.12 kJ/mol, ΔS = 41.72J/ (mol K), and ΔG298 = -19.55 kJ/mol, respectively. The kinetics of adsorption follows the Brykina's equation with the rate constant k298 = 1.06 × 10-4 s-1.